2020
DOI: 10.1093/cercor/bhaa370
|View full text |Cite
|
Sign up to set email alerts
|

Data-Driven Classification of Spectral Profiles Reveals Brain Region-Specific Plasticity in Blindness

Abstract: Congenital blindness has been shown to result in behavioral adaptation and neuronal reorganization, but the underlying neuronal mechanisms are largely unknown. Brain rhythms are characteristic for anatomically defined brain regions and provide a putative mechanistic link to cognitive processes. In a novel approach, using magnetoencephalography resting state data of congenitally blind and sighted humans, deprivation-related changes in spectral profiles were mapped to the cortex using clustering and classificati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 160 publications
(252 reference statements)
0
19
0
Order By: Relevance
“…Auditory spectral profiles turned out to be modulated during auditory processing. Lubinus and colleagues [14] have discovered that visual deprivation is reflected in the modulation of spectral fingerprints, indicating possible correspondence with the structural and functional adaptation of the human brain. Likewise, Mellem with collaborators [6] demonstrated via a similar method that there is a mix of lower and higher frequency peaks across the brain and it does not follow a simple lower order-higher order processing hierarchy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Auditory spectral profiles turned out to be modulated during auditory processing. Lubinus and colleagues [14] have discovered that visual deprivation is reflected in the modulation of spectral fingerprints, indicating possible correspondence with the structural and functional adaptation of the human brain. Likewise, Mellem with collaborators [6] demonstrated via a similar method that there is a mix of lower and higher frequency peaks across the brain and it does not follow a simple lower order-higher order processing hierarchy.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, spectral profiles' peaks that correspond to the natural frequencies of ROIs [12], [13], are consistently modulated by specific tasks, neurological or mental disorders. They can be generalized across groups of participants [14], [7]. In this paper, we introduce a novel implementation of the Spectral Fingerprinting technique, in a highly configurable MATLAB toolbox.…”
Section: Introductionmentioning
confidence: 99%
“…83 Previous EEG studies in CB and CC individuals have repeatedly observed lower alpha oscillatory activity 51,53,54 and in CB individuals higher gamma oscillatory activity. 55,56 Alpha oscillatory activity has been considered to be an electrophysiological signature for the control of the excitatory/inhibitory (E/I) balance of neural circuits. 84 In the present context, it is important to note that alpha oscillatory activity has been found to inversely correlate with ALFF, [45][46][47]85 while gamma band activity was found in monkeys to positively correlated with slow BOLD fluctuations.…”
Section: Discussionmentioning
confidence: 99%
“…[51][52][53][54] Moreover, two MEG studies later reported enhanced gamma activity in congenitally permanently blind individuals compared to typically sighted controls. 55,56 Recent studies have suggested that alpha and gamma oscillatory activity indicate antagonistic mechanisms with alpha oscillations controlling gamma oscillatory activity. 57,58 Interestingly, in monkeys it has been observed that slow BOLD fluctuations correlated with high frequency local field potentials (LFP) in the gamma range particularly in an eyes closed condition.…”
Section: Introductionmentioning
confidence: 99%
“…54–57 Moreover, two magnetoencephalography studies later reported enhanced gamma activity in congenitally permanently blind individuals compared with typically sighted controls. 58 , 59 Recent studies have suggested that alpha and gamma oscillatory activity indicate antagonistic mechanisms with alpha oscillations controlling gamma oscillatory activity. 60 , 61 Interestingly, in monkeys, it has been observed that slow BOLD fluctuations positively correlate with high frequency local field potentials (LFPs) in the gamma range particularly in an EC condition.…”
Section: Introductionmentioning
confidence: 99%